The orientational order and the dynamics of the dendritic liquid crystal organo-siloxane tetrapodes determined using dielectric spectroscopy - VIJ, JAGDISH (My University, 2006)
The dielectric measurements have been carried out on the two zeroth generation dendrimers with four branched arms (called tetrapodes) based on the siloxane cores. The results are analyzed in the framework of the molecular theory of dielectric permittivity by Maier and Meier for nematogens. At least four molecular processes are resolved in the dielectric relaxation spectra in the nematic phase for each of the two tetrapodes. Three of them are assigned to the reorientation of the monomeric unit whereas the fourth is assigned to the rotation of the molecular segments in the individual arms of the monomeric unit around the long molecular axis. The dielectric relaxation strength of the low frequency process has been used to calculate the orientational order parameter. The dynamics of the resolved processes has been quantitatively analyzed using the results of the microscopic model of the rotational diffusion, given by Coffey and Kalmykov [W. T. Coffey and Yu. P. Kalmykov, Adv. Chem. Phys. 113, 487 (2000)] using the calculated order parameter. All molecular processes: the rotation around the short molecular axis (end-over-end rotation), precession around the director and the rotation around the long molecular axis (also called the spinning motion) are shown to have successfully been reproduced by the model. The anisotropy of the rotational diffusion coefficients gradually increases with a reduction in temperature, to a factor of 3 in the nematic phase relative to its isotropic phase
PUBLISHED
Keywords: Electronic & Electrical Engineering